Penerapan Metode Yanbu’a dalam Meningkatkan Kemampuan Membaca Al-Qur’an Siswa Kelas V di MI Al-Muhsin 1 Krapyak Wetan Bantul Yogyakarta - Fairuz Zunaidah Rohmi; Mangun Budiyanto (Laboratorium Pendidikan Fakultas Ilmu Tarbiyah dan Keguruan, 2020)
This study aims to find out how the application of the Yanbu’a method in improving the reading ability of the Qur’an in class V students at MI Al-Muhsin 1 Krapyak Wetan Bantul Yogyakarta. This research is a descriptive qualitative research with data collection using interview, observation, and documentation techniques. Data analysis techniques with data reduction, data presentation, and drawing conclusion. The results of this study namely, in the beginning the method of learning the Qur’an at MI Al-Muhsin 1 used the method of Qiro’ati. Then switch to using the Yanbu’a method for some consideration. The implementation of learning the Qur’an using the method of Yanbu’a implemented as learning in general opening activities, core activities, and closing activities. As for the evaluation of learning done every day and every volume increase. In the implementation of learning the Qur’an using the methods of Yanbu’a. there are several supporting factors, namely a competent teacher, student backgorund, adequate facilities, and support from parents. There are also inhibiting factors in the implementation of the Yanbu’a method namely teacher delay, the attitude of students, parents who only rely on reading the Qur’an in the madrasa, the absence of Yanbu’a training by madrasa and the absence of evaluation for Yanbu’a instructors. The results of the application of the Yanbu’a method in improving the ability to read the Qur’an students based on student achievement data, 13 students out of 25 students who study using the method of Yanbu’a have reached volume 5, 6, and 7 with a percentage of 52%. Keywords: Yanbu’a Method, Al-Qur'an Learning, Ability to Read the Qur'an